Development of Student Worksheet Based on Contextual for Sixth Grade Students at MI Al-Usman Malang: English - Muhammad Fajrul Falah; Tyas Alhim Mubarok; Ahmad Saifudin (Journal of English Development, 2023)
The research's objective is to describe the process of developing contextual-based student worksheets while at the same time knowing the results of developing contextual-based student worksheets for students. To achieve this goal, the type of research used is Research and Development (R&D). Data collection techniques in this study were validation questionnaires and student responses. Data were analyzed through the level of validity and practicality of student worksheets (LKS) using a predetermined formula. The results of this development have resulted in student worksheets being declared very valid by students’ worksheet and material design experts with an average value of 92%. Student satisfaction response questionnaire obtained by 90% can be said to be very practical. The conclusion of the study is that the use of student worksheets (LKS) can improve the vocabulary mastery of MI Al - Usman class VI Kedungkandang Malang students, especially in the ability to understand concrete learning